1988
DOI: 10.1152/ajprenal.1988.255.6.f1191
|View full text |Cite
|
Sign up to set email alerts
|

Renal tubular cells are potential targets for epidermal growth factor

Abstract: Epidermal growth factor (EGF) is a potent polypeptide mitogen with various receptor-mediated growth effects on cells from the skin, breast, and gastrointestinal tract. Recent studies indicate that EGF is produced in the kidney and is excreted in the urine, but the biological significance of renal EGF is uncertain. We demonstrate in vitro mitogenicity of EGF for LLC-PK1 cells, a tubular epithelial cell line derived from pig kidney cortex. Furthermore, when subconfluent monolayers of LLC-PK1 cells are exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…Thus, we proceeded with functional studies using the LLC-PK 1 PKD2 cells. Previous work had demonstrated that LLC-PK 1 cells express endogenous PKD2 and functional EGFR (16,19,25,28,42). Initial single channel recordings in cell-attached patches of LLC-PK 1 PKD2 cells indicated the existence of an EGF-activated channel with a conductance in K ϩ higher than that in Na ϩ or in Ca 2ϩ (see the supplemental material).…”
Section: Egf-induced Currents Are Enhanced In Llc-pkmentioning
confidence: 97%
“…Thus, we proceeded with functional studies using the LLC-PK 1 PKD2 cells. Previous work had demonstrated that LLC-PK 1 cells express endogenous PKD2 and functional EGFR (16,19,25,28,42). Initial single channel recordings in cell-attached patches of LLC-PK 1 PKD2 cells indicated the existence of an EGF-activated channel with a conductance in K ϩ higher than that in Na ϩ or in Ca 2ϩ (see the supplemental material).…”
Section: Egf-induced Currents Are Enhanced In Llc-pkmentioning
confidence: 97%
“…Furthermore, Amsler et al [21]reported that LLC–PK1 cells regulate the rate of sodium–dependent amino acid transport during growth. Goodyer et al [12]also reported that the sodium–dependent phosphate uptake in LLC–PK1 cells was stimulated by EGF only in subconfluent cells. These authors suggested that the disappearance of the effect on phosphate uptake is related to the effect of cell–cell contacts on the EGF response.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the LLC–PK1 cell line expresses different types of G–protein–coupled receptor systems [10, 11]and demonstrates a proliferative response to the protein tyrosine kinase stimulating growth factor, EGF [12]. It has also been reported that 12– o –tetradecanoylphorbol–13–acetate (TPA) stimulates sodium–coupled phosphate and amino acid transport in LLC–PK1 cells via activation of protein kinase C [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Though there is some experimental evidence for glomerular action of renal EGF in the rat [25], the best-documented function of EGF is to maintain distal nephron integrity and func tion [8][9][10]. In addition, it may regulate renal hemody namics, as suggested by the finding that urinary EGF excretion correlates directly with renal blood flow in women affected by arterial hypertension (r = 0.73, n = 13. p < 0.01) [personal unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…A specific messenger RNA for the EGF precursor is present in the kidney at the level of thick ascending limb of Henle's loop, and early distal convoluted tubule [4], Synthesis of EGF by the kidney suggests the possibil ity of a local biological function. Similar to the protec tive and repairing effect exerted by EGF in the gastroin testinal apparatus [7], the action of renal EGF may serve as a trophic function for the distal urinary epithelium and promote renal cell mitogenic response after loss of nephron [8]. In addition, the findings that EGF affects sodium absorption in isolated perfused segments of rab bit cortical collecting tubules [9.…”
Section: Introductionmentioning
confidence: 99%